The synthesis and physical properties of semipermeable polymeric membranes used in water purification by the process of reverse osmosis - Pienaar, H. S.(Hendrik Schalk) (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph. D.) -- University of Stellenbosch, 1977.